Impact of VSD therapy on surgical outcomes, inflammatory markers, and functional rehabilitation in patients with secondary bone infection following tibial fracture surgery - Sheng Chang; Yu Wang; Zengshan Zhang (Frontiers in Cellular and Infection Microbiology)
ObjectiveThe aim of this study was to investigate the effect of vacuum sealing drainage (VSD) treatment on surgical indicators, inflammatory factors, and functional recovery in patients with chronic osteomyelitis secondary to open tibial fractures.MethodsIn total, 87 patients with secondary bone infection after internal fixation of tibial fracture treated in the Affiliated Hospital of Shandong Second Medical University from December 2020 to June 2022 were selected, all of whom were tibial shaft fractures. Of these, 55 cases of primary open fracture were sutured in the first stage; 32 cases underwent internal fixation after primary debridement at the time of trauma. The patients were treated with surgical debridement, removal of internal fixation, and fixation with an external fixation frame. After debridement, those with local wounds that could not be completely closed and were complicated with exposed bone were randomly selected for either VSD covering treatment (study group, n=46) or bone cement covering treatment (control group, n=41. The distribution of pathogenic bacteria, surgical indicators, inflammatory factors [tumor necrosis factor⁃α(TNF⁃α), interleukin⁃6 (IL⁃6), and C⁃reactive protein (CRP) levels], functional recovery [knee, ankle, and limb function recovery], and complications were summarized.ResultsThere were 87 pathogenic bacteria strains in 87 patients, including 43 Gram⁃positive bacteria strains (49.42%), 32 Gram⁃negative bacteria strains (36.78%), and 12 fungi strains (13.80%). The number of dressing changes in the study group was less than that in the control group. The infection control time, wound sterility time, hospitalization time, and skin flap transfer operation time in the study group were shorter than those in the control group and the difference was statistically significant (P<0.05). After treatment, the levels of TNF⁃α, IL⁃6, and CRP in the two groups decreased, among which the change in the study group was the most significant and the difference between the two groups was statistically significant (P<0.05). After treatment, the Hospital for Special Surgery Knee Score and Baird–Jackson score of the two groups increased, among which the change in the study group was the most significant and the difference between the two groups was statistically significant (P<0.05). The excellent and good rate of the study group (95.65%) was higher than the excellent and good rate of the control group (80.49%) and the difference was statistically significant (P<0.05).ConclusionWhen a wound cannot be closed, VSD treatment of patients with secondary bone infection after internal fixation of tibial fracture can improve the level of surgical indicators and inflammatory factor levels in patients, and promote the recovery of patients’ limb function, and is thus worthy of clinical promotion and application.